The Development of an On-line Submission and Peer Review System - Pavey, Paul; Probets, Steve; Brailsford, David F. (ICCC Press, 2000)
Online submission and peer review is emerging as the next step forward for many journal publishers in an ever increasing drive to take advantage of technological improvements in transferring data electronically over the internet. The Electronic Submission and PEer REview (ESPERE) project was initiated in 1996 as an electronic Libraries (eLib) initiative of the Higher Education Funding Council for England (HEFCE). Subsequently the project continued as a self-funding group composed of a consortium of learned society and commercial journal publishers intent on utilising the changes in technology to improve the services they provide to their authors as well as cutting their costs and increasing efficiencies.